A contact relation analysis approach to assembly sequence planning for assembly models. Issue 6 (19th September 2017) - Tao, Songqiao; Hu, Min
ABSTRACT: A reasonable assembly planning can obviously reduce manufacturing time and costs. From the perspective of geometric reasoning in reverse, a contact relation analysis approach to ASP for assembly models is proposed in this paper. The main characteristic of the presented method has an ability to choose non-orthogonal assembling directions automatically. Firstly, contact relations between parts of an assembly model are automatically extracted from its CAD model. According to contact relations, contact vectors are generated. Secondly, the disassembly of a part in an assembly model is checked. Based on extracted contact vectors, instantaneous movable directions for parts are identified by solving inequality constraints. And Gaussian sphere is introduced to express a set of movable directions. Subsequently, currently removable parts are judged by checking the existence of feasible disassembly paths along instantaneous movable directions. Thirdly, different layers of removable parts in an assembly are obtained based on extracted assembly relations and geometric removable judgment. Using the contact state transition analysis of layer graphs of AS and the knowledge of the assembly process, the final assembly sequence of craft viable can be found. Finally, an example has been provided to demonstrate the proposed approach. GRAPHICAL ABSTRACT: